Spread spectrum : performance comparison in linear and non-linear system / Hazril Majid Abdul Hamid - Abdul Hamid, Hazril Majid (2002)
Spread spectrum is one of the most popular transmission system used widely in satellite communications for its signal security. It is called spread spectrum because the transmission bandwidth employed is much greater than the minimum bandwidth required to transmit the information signal. Satellite power for transmission is expensive and for terrestrial transmissions, a rate limited power amplifier is used, which ideally permits no amplitude variation in the transmitted signal. In this thesis, the performance of linear system and non-linear system is being compared using mathlab Simulink simulation software. The received signal in both linear and nonlinear system will be compared with the transmitted signal in the existence of Additive White Gaussian Noise (AWGN) in the channel. The bit error rate and error curve will determine the better system for spread spectrum transmission.